Photocatalyzed synthesis of isochromanones and isobenzofuranones under batch and flow conditions - Anselmo, Manuel; Moni, Lisa; Ismail, Hossny; Comoretto, Davide; Riva, Renata; Basso, Andrea (Beilstein Journal of Organic Chemistry, 2017)
Photocatalyzed reactions of 2-(alkoxycarbonyl)benzenediazonium tetrafluoroborates with various alkenes afforded isochromanones in good yields, according to a mechanism that was investigated. The advantage of using highly soluble esters rather than carboxylic acids as starting compounds became evident when the reactions were performed under flow conditions. On the other hand, when 2-vinylbenzoic acid derivatives were employed as reagents, isobenzofuranones were obtained together with unprecedented benzo[e][1,3]oxazepin-1(5H)-ones, with the latter derived from incorporation of the solvent (acetonitrile).
Keywords: flow chemistry; heterocycles; multicomponent reactions; photocatalysis; photo-Meerwein arylation–addition